Faktor-Faktor Yang Berhubungan Dengan Perilaku Merokok Pada Remaja Smpn 18 Kota Jambi Tahun 2026 - Vebby Markorolina; Puspita Sari; Ashar Nuzulul Putra; M. Ridwan; Muhammad Rifqi Azhari (Jurnal Multidisipliner Bharasumba, 2026)
Smoking behavior among adolescents remains a public health concern influenced by various factors. This study aimed to analyze the factors associated with smoking behavior among adolescents at SMPN 18 Jambi City. A quantitative study with a cross-sectional design was conducted involving 89 students selected through simple random sampling. Data were collected using a structured questionnaire and analyzed using univariate and bivariate analyses with the Chi-square test at a 95% confidence level. The results showed that most respondents exhibited smoking behavior (57.3%). Bivariate analysis revealed significant associations between smoking behavior and knowledge (p = 0.025), attitude (p = 0.000), parental influence (p = 0.000), peer influence (p = 0.001), cigarette advertising exposure (p = 0.009), psychological factors (p = 0.000), and facilities and infrastructure (p = 0.000). It can be concluded that all of these factors were significantly associated with adolescent smoking behavior. Schools are encouraged to strengthen health education, improve supervision, and actively involve parents in smoking prevention efforts among adolescents.